Partial purification and characterization of two cytoplasmic DNA polymerases from ungerminated wheat. - Castroviejo, M (1975)
Two DNA polymerases have been purified from the 105,000 x g supernatant of ungerminated wheat. The purification stages included: high speed centrifugation, salt fractionation, DEAE-cellulose chromatography, Sephadex G-150 filtration and phosphocellulose chromatography. Several properties of the two enzyme (called A and B according to the order of elution from the phosphocellulose column) have been studied. Enzyme A has a sedimentation coefficient of about 7 S, utilizes activated DNA and synthetic polydeoxynucleotides as well as poly rA-dT12, while B has a sedimentation coefficient of about 6.2 and uses only activated DNA and synthetic polydeoxynucleotides as templates. Other parameters like KCl effect, MnCl2 effect, optimum pH, etc. Allow us to distinguish clearly between both DNA polymerases.